Testicular Pain and Mesenteric Adenitis as an Atypical Presentation of COVID-19 - Desai, Shreya (Cureus, 2021)
A 21-year-old Caucasian male with no past medical history presented to the emergency department with right lower quadrant pain radiating to the right testicle for two days. He reported an occasional dry cough that day but denied any fever or other infectious symptoms. The patient was afebrile with a normal physical examination. CT of the abdomen and pelvis showed prominent right lower quadrant lymphadenopathy. Viral panel for common respiratory pathogens returned negative. A nasopharyngeal swab for SARS-CoV-2 by Xpert® Xpress SARS-CoV-2 reverse transcriptase-polymerase chain reaction (Cepheid Inc., Sunnyvale, CA) was positive. The patient remained in quarantine for 14 days. He was reevaluated seven weeks later with spontaneous resolution of his abdominal pain and the continued absence of upper respiratory symptoms. A repeat CT scan seven weeks later showed persistent mesenteric lymphadenopathy. Repeat COVID-19 testing was not performed at this time. While the frequency of atypical presentation of COVID-19 remains unknown, healthcare providers must continue to remain vigilant and consider COVID-19 as a differential diagnosis in any patient presenting to the emergency department despite the lack of respiratory and gastrointestinal symptoms. Further research is warranted to examine the possibility of asymptomatic spread in asymptomatic patients with persistent radiologic findings and to assess whether repeat COVID-19 testing is warranted in such patients.